1995
DOI: 10.1093/carcin/16.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the immortalization of mammalian cells by ionizing radiation and chemical carcinogens

Abstract: Immortalization is a prerequisite for the clonal evolution and malignant transformation of normal mammalian cells in culture. In order to gain a mechanistic insight into the genetics of carcinogen-induced cellular immortality, a cell culture assay has been developed based on the use of freshly explanted Syrian hamster dermal (SHD) fibroblasts. The relative efficacies of a variety of chemical and physical carcinogens at immortalizing SHD cells (against a zero background of spontaneous immortalization) were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 26 publications
3
62
0
Order By: Relevance
“…Moreover, carcinogens, particularly radiations and mutagenic chemical carcinogens, induce aneuploidy without delay, and thus long before cancer [170][171][172][173][174], as postulated by the chromosomal theory. Most importantly, our own studies have shown that among the many effects that carcinogens have on cells [40], aneuploidy is the one that consistently segregates with subsequent carcinogenesis [84,170].…”
Section: Carcinogens Function As Aneuploidogensmentioning
confidence: 99%
“…Moreover, carcinogens, particularly radiations and mutagenic chemical carcinogens, induce aneuploidy without delay, and thus long before cancer [170][171][172][173][174], as postulated by the chromosomal theory. Most importantly, our own studies have shown that among the many effects that carcinogens have on cells [40], aneuploidy is the one that consistently segregates with subsequent carcinogenesis [84,170].…”
Section: Carcinogens Function As Aneuploidogensmentioning
confidence: 99%
“…The absence of chromosomal aberrations in nickel-transformed cells suggests that DNA methylation may be a mechanism of transformation by nickel treatment. 5,56,57 Furthermore, chromosome transfer experiments demonstrate that the unlimited proliferative character of a nickel-transformed cell line could be reversed by induction of senescence. The senescence gene(s) is located in the donor X-chromosome, and its expression is regulated by DNA methylation, as treatment of cells with 5-aza restores the senescence capacity of donor cells.…”
mentioning
confidence: 99%
“…The SHD cell system has previously been used successfully to measure events at frequencies of 1 × 10 -5 (Trott et al, 1995). Here, we have adapted the published procedure to incorporate tenfold more cells and thus increase the sensitivity of the assay to permit visualization of events which could occur at the extremely low frequencies suggested by human epidemiological studies.…”
Section: Experimental Designmentioning
confidence: 99%
“…Syrian hamster dermal (SHD) cells, however, have proved valuable as a model, low background cell immortalization system to assess the carcinogenicity of various agents, including soluble nickel which, like EMFs, does not directly damage DNA (Trott et al, 1995). This system can detect events at frequencies of less than 1 in 10 6 over a background immortalization frequency of less than 1 in 10 9 .…”
mentioning
confidence: 99%